Risk Factors Association for MRSA Nasal Colonization in Preoperative Patients in Azadi Teaching Hospital-Duhok, Kurdistan Region, Iraq - Abdulkareem, Warveen L.; Hussein, Nawfal R.; Mohammed, Ayad A.; Arif, Sardar H.; Naqid, Ibrahim A. (Science Journal of University of Zakho, 2020)
Background: Nasal colonization with Methicillin-resistant Staphylococcus aureus (MRSA) can predispose to subsequent infections in surgical and non-surgical patients, making the management challenging with increased rates of morbidity, mortality and cost burden. Objectives: The present study was carried out to evaluate the risk factors of MRSA nasal colonization in preoperative patients in Azadi Teaching Hospital in Duhok Province - Kurdistan Region-Iraq. Methods: Nasal swabs were obtained from 150 patients after completing a questionnaire. Conventional laboratory methods were carried out to identify Staphylococcus aureus (S. aureus) and antimicrobial susceptibility test was conducted for recognizing MRSA isolates. Results: A total of 41 (27.3%) of 150 patients were MRSA carriers. The mean age of participants MRSA carriers was 35.27±20.40 years old. The highest prevalence rate of nasal colonization with MRSA was in males (27.94%) than females (26.82%). In logistic regression analysis, no significant differences was detected between MRSA carriage and the associated risk factors including age [OR: 0.99 (95 % CI: 0.97- 1.01); P = 0.45], gender [OR: 1.05 (95 % CI: 0.51- 2.17); P = 0.87] and medical comorbidities [OR: 1.11 (95 % CI: 0.42- 2.92); P = 0.82]. Conclusions: Age, gender and medical comorbidities were not associated common risk factors for nasal colonization of MRSA in preoperative patients. This study should be considered preliminary and studies with larger sample sizes and with using advance molecular tools are needed in the future.